Microsoft Forefront threat management gateway (TMG) administrator's companion - Harrison, Jim (Microsoft Press, 2010)
Get your Web security, network perimeter security, and application layer security gateway up and running smoothly. This indispensible, single-volume reference details the features and capabilities of Microsoft Forefront Threat Management Gateway (TMG). You'll gain the real-world insights, implementation and configuration best practices, and management practices you need for on-the-job results. Discover how to: Implement TMG integrated security features Analyze your Web and perimeter security requirements and infrastructure Plan, install, and configure TMG Implement network intrusion prevention, proxy, caching, filtering Configure security for the Web, Microsoft Exchange Server, and SharePoint Products and Technologies Implement remote access and site-to-site VPNs Select and configure clients Monitor and troubleshoot protected systems with Network Monitor 3 and other tools Use scripting to configure systems and automate administration Plus, get a fully searchable eBook on the companion CD For customers who purchase an ebook version of this title, instructions for downloading the CD files can be found in the ebook.
Cover title. - Print version record
Keywords: Microsoft Forefront Threat Management Gateway; Computer security -- Software; Computer security -- Management; Sécurité informatique; Logiciels; Sécurité informatique; Gestion; COMPUTERS; Computer Literacy; COMPUTERS; Computer Science; COMPUTERS; Data Processing; COMPUTERS; Hardware; General; COMPUTERS; Information Technology; COMPUTERS; Machine Theory; COMPUTERS; Reference; Computer security; Software; Computer security; Management; Computer security; Software